Pregnancy Complications in a-Thalassemia (Hemoglobinopathy H): A Case Study. (27th May 2018) - Politou, Marianna; Dryllis, Giorgos; Efstathopoulou, Maria; Valsami, Serena; Triantafyllou, Faidra-Evangelia; Tsaroucha, Athanasia; Kattamis, Antonios; Vlahos, Nikos F.
Abstract : Thalassemia intermedia (TI) is a clinical definition which represents a wide spectrum of thalassemia genotypes but mainly includes patients who do not require or only occasionally require transfusion. An uncommon case of a 32-year-old Greek woman, para 1, at the 22nd week + day 3 of gestation with thalassemia intermedia (she was splenectomized), where her pregnancy was complicated with portal vein thrombosis, splenic thrombosis, and partial HELLP, is described. This is a generally uncommon event in thalassemia intermedia. She had no transfusion as her hematologist consulted and she took anticoagulation therapy. Thus, we present for the first time in the literature a case of HbH a-thalassemia pregnant woman whose pregnancy was complicated with portal vein thrombosis, splenic vein thrombosis, and partial HELLP; she was treated with anticoagulation therapy and she had a successful outcome.